Autokorelasi Spasial Kejadian Demam Berdarah Dengue (DBD) di Kota Medan Tahun 2023 - Savina Talitha Jasmine (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the spatial autocorrelation of Dengue Hemorrhagic Fever (DHF) cases in Medan City in 2023 by considering the number and density of the population. An ecological study approach was used with 21 sub-districts as the analysis unit. Secondary data were analyzed using the Local Indicators of Spatial Association (LISA) method through GeoDa software. The results show that globally there is no significant spatial autocorrelation between DHF cases and the number or density of the population. However, locally, positive spatial interactions were found in three sub-districts, namely Medan Selayang, Medan Tuntungan, and Medan Petisah. These three areas show the potential for high-risk clusters. These results indicate that the distribution of DHF in Medan City is heterogeneous and influenced by spatial and demographic factors. Therefore, DHF control requires a region-based approach and the use of geographic information systems (GIS) to support more effective and targeted public health policies.